Sarcocystis spp. and Toxoplasma gondii in muscles from wild boars (Sus scrofa) consumed in Switzerland - Moré, Gastón Andrés (2025)
Sarcocystis spp. and Toxoplasma gondii are heteroxenous protozoan parasites, which form cysts in muscle tissue of intermediate hosts (IH) and oocysts in the intestinal mucosa of definitive hosts (DH). Wild boars (Sus scrofa) are IH for Sarcocystis miescheriana (with wild and domestic canids as DH), S. suihominis (with humans and nonhuman primates as DH) and T. gondii (with felids as DH). The aim of this study was to identify and characterize Sarcocystis spp. and T. gondii in the muscle tissue of wild boars hunted and/or consumed in Switzerland. DNA was extracted from muscle samples of 286 wild boars and tested by PCRs targeting the 18S rRNA gene of Sarcocystis spp., the mitochondrial cytochrome c oxidase (cox1) gene of S. suihominis and by a qPCR targeting a 529 bp genomic repeat of T. gondii. Besides, 225 samples were processed by homogenization and direct microscopic examination and 42 samples by histopathology. Sarcocysts were detected microscopically in 89.3 % (201/225) and 35.7 % (15/42) of the samples, respectively. The 18S rRNA PCR detected parasite DNA in 91.3 % (261/286) of the samples, and all 62 sequences obtained were 100 % identical, and also with GenBank sequences reported as S. miescheriana, suggesting a high environmental contamination with canid faeces. The S. suihominiscox1 PCR was positive in 1.75 % of the samples (5/286), and the six cox1 sequences (772 bp primers trimmed) obtained were 97.3–99.6 % similar among them and 97.7–100 % identical with a sequence reported as S. suihominis. Despite the identity differences, all these sequences were grouped together in a phylogenetic tree, in a sister clade of S. miescheriana sequences. All samples tested negative for T. gondii by qPCR. This study revealed for the first time the presence of S. suihominis in wild boars hunted in Switzerland.